Essential oils as reagents in green chemistry - Li, Ying; Fabiano-Tixier, Anne-Sylvie; Chémat, Farid (SpringerBriefs in molecular science. Green chemistry for sustainability., 2014)
This brief provides a valuable reference for the contribution of essential oils in the green chemistry, mainly in terms of their characteristics corresponding to their compositions, the development of their extraction technologies including both conventional and green process (e.g. microwave, ultrasound), and their sustainable applications as antioxidants, antimicrobials, insecticides, green solvents and synthons for the green synthesis.